Assessing Unwanted Variations in Rheumatology Clinic Previsit Rooming - Edmond Ramly; Brad Stroik; Diane Lauver; Heather M. Johnson; Patrick E. McBride; Kristin Lewicki; Jón Árnason; Christie M. Bartels (2018)
Rheumatologists face time pressures similar to primary care but have not generally benefitted from optimized team-based rooming during the time from the waiting room until the rheumatologist enters the room.The aim of this study was to assess current capacity for population management in rheumatology clinics; we aimed to measure the tasks performed by rheumatology clinic staff (medical assistants or nurses) during rooming.We performed a cross-sectional time-study and work-system analysis to measure rooming workflows at 3 rheumatology clinics in an academic multispecialty practice during 2014-2015. We calculated descriptive statistics and compared frequencies and durations using Fisher exact test and analysis of variance.Observing 190 rheumatology clinic previsit rooming sequences (1419 minutes), we found many significant variations. Total rooming duration varied by clinic (median, 6.75-8.25 minutes; p < 0.001). Vital sign measurement and medication reconciliation accounted for more than half of rooming duration. Among 3 clinics, two of 15 tasks varied significantly in duration, and 9 varied in frequency. Findings led clinic leaders to modify policies and procedures regarding 6 high-variation tasks streamlining assessment of weight, height, pain scores, tobacco use, disease activity, and refill needs.Assessing rheumatology rooming tasks identified key opportunities to improve quality and efficiency without burdening providers. This project demonstrated user-friendly methods to identify opportunities to standardize rooming and support data-driven decisions regarding rheumatology clinic practice changes to improve population management in rheumatology.